Genomic inbreeding estimation, runs of homozygosity, and heterozygosity-enriched regions uncover signals of selection in the Quarter Horse racing line - Santos, Wellington B. [UNESP]; Pereira, Camila B. [UNESP]; Maiorano, Amanda M.; Arce, Cherlynn D. Silva [UNESP]; Baldassini, Welder A. [UNESP]; Pereira, Guilherme L. [UNESP]; Chardulo, Luis Artur L. [UNESP]; Neto, Otávio R. M. [UNESP]; Oliveira, Henrique N. [UNESP]; Curi, Rogério A. [UNESP] (Wiley, 2023)
With the advent of genomics, significant progress has been made in the genetic improvement of livestock species, particularly through increased accuracy in predicting breeding values for selecting superior animals and the possibility of performing a high-resolution genetic scan throughout the genome of an individual. The main objectives of this study were to estimate the individual genomic inbreeding coefficient based on runs of homozygosity (FROH), to identify and characterize runs of homozygosity and heterozygosity (ROH and ROHet, respectively; length and distribution) throughout the genome, and to map selection signatures in relevant chromosomal regions in the Quarter Horse racing line. A total of 336 animals registered with the Brazilian Association of Quarter Horse Breeders (ABQM) were genotyped. One hundred and twelve animals were genotyped using the Equine SNP50 BeadChip (Illumina, USA), with 54,602 single nucleotide polymorphisms (SNPs; 54K). The remaining 224 samples were genotyped using the Equine SNP70 BeadChip (Illumina, USA) with 65,157 SNPs (65K). To ensure data quality, we excluded animals with a call rate below 0.9. We also excluded SNPs located on non-autosomal chromosomes, as well as those with a call rate below 0.9 or a p-value below 1 × 10−5 for Hardy–Weinberg equilibrium. The results indicate moderate to high genomic inbreeding, with 46,594 ROH and 16,101 ROHet detected. In total, 30 and 14 candidate genes overlap with ROH and ROHet regions, respectively. The ROH islands showed genes linked to crucial biological processes, such as cell differentiation (CTBP1, WNT5B, and TMEM120B), regulation of glucose metabolic process (MAEA and NKX1-1), heme transport (PGRMC2), and negative regulation of calcium ion import (VDAC1). In ROHet, the islands showed genes related to respiratory capacity (OR7D19, OR7D4G, OR7D4E, and OR7D4J) and muscle repair (EGFR and BCL9). These findings could aid in selecting animals with greater regenerative capacity and developing treatments for muscle disorders in the QH breed. This study serves as a foundation for future research on equine breeds. It can contribute to developing reproductive strategies in animal breeding programs to improve and preserve the Quarter Horse breed.
Keywords: autozygosity; Equus caballus; signatures of selection; SNP array